2015
DOI: 10.1111/1754-9485.12273
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of diffusion‐weighted imaging and the apparent diffusion coefficient values in the differentiation of benign and malignant breast lesions

Abstract: DWI can be an effective radiological method in the differentiation of benign and malignant breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The motion of water molecules in tissue can be affected by tissue cellularity and membrane integrity [6]. DWI has been applied in the detection of breast cancer [34], differentiation of benign and malignant lesions [35], and monitoring the response to neoadjuvant chemotherapy [36,37]. However, there is no consensus that DWI is a reliable stand-alone method.…”
Section: Discussionmentioning
confidence: 99%
“…The motion of water molecules in tissue can be affected by tissue cellularity and membrane integrity [6]. DWI has been applied in the detection of breast cancer [34], differentiation of benign and malignant lesions [35], and monitoring the response to neoadjuvant chemotherapy [36,37]. However, there is no consensus that DWI is a reliable stand-alone method.…”
Section: Discussionmentioning
confidence: 99%
“…However, high sensitivity leads to the problem of over-treatment, resulting in a high rate of puncture biopsies [ 17 19 ]. Many studies have tested the effectiveness of DWI in benign-malignant differentiation of breast lesions and find that ADC values can increase the specificity of breast MRI [ 20 , 21 ]. For example, Li et al [ 22 ] found that ADC values were significantly lower in malignant than in benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Often, but not always, cancerous breast tissue is associated with increased cellularity and increased intracellular density, such that the motion of water is diminished, and the apparent diffusion coefficient (ADC) is lowered. On the other hand, the ADC is often increased with non-cancerous breast lesions [50][51][52]. There are, however, exceptions: fibrotic or benign proliferative processes are also associated with diminished ADC, whereas necrotic tissue within a cancer is hypocellular, and, therefore, associated with increased ADC.…”
Section: Diffusion-weighted Imaging For Identifying Breast Cancer Andmentioning
confidence: 99%